Analisis Diversitas Qalbu Manusia - Mahdi Mahdi; Warul Walidin AK Warul Walidin; Salami Mahmud Salami (ISTIFHAM, 2023)
The analysis of the diversity of the human heart is an effort to understand the differences in the diversity and variation of the human heart itself. This research is descriptive with content analysis based on library research. The results of the analysis show that according to the type and function of the heart consists of twenty types including: Qalbun Salim, Qalbun Munib, Qalbun mukhbit, Qalbun wajil, Qalbun taqiy, Qalbun Mahdiy, Qalbun muthmainnun, Qalbun hayy, Qalbun Maridh, Qalbun a'ma, Qalbun lahiy , Qalbun atsim, Qalbun mutakabbir, Qalbun ghalizh, Qalbun makhtum, Qalbun qasiy, Qalbun Ghafil, Qalbun aghfal, Qalbun zaigh, and Qalbun murib. The heart's activity includes rational ability/cognitive ability, emotional ability and spiritual ability. Functionally, the heart performs the following activities: al-fikru, (to think), adz-dzikru, (to remember), an-nazhru, (to look/have), ar-ra'yu, (to see/respond), al -'aqlu, (to outwit/think), ad-dabru, (to think deeply), al-fiqhu, (to understand/know), al-'ibrah, (to learn), as-sam'u , (to hear) and al-bashru, (to see).